Supplementary Figure 1 from Metastatic Prostate Cancers with BRCA2 versus ATM Mutations Exhibit Divergent Molecular Features and Clinical Outcomes - Justin Hwang (15925675) (2025)
Overall survival of ATM, BRCA2 mutant, and HRDother mPCs.